2018
DOI: 10.1111/vru.12672
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography is more accurate than percutaneous palpation for identifying targeted thoracolumbar intervertebral disc spaces in dogs

Abstract: During minimally invasive spinal surgery, correct identification of the affected intervertebral disc space is critical. Percutaneous palpation is commonly used, but results may be unreliable. Fluoroscopy is the gold standard but can be cumbersome and exposes operators to ionizing radiation. Spinal ultrasound has been described in veterinary medicine and could be a feasible alternative. This prospective, methods comparison study mimicked a minimally invasive spinal surgery in 10 canine cadavers and compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Percutaneous needle placement and preoperative radiography may also represent a simple alternative to intraoperative fluoroscopy. Palpation or ultrasonography can also be used for site localization, with the latter being more accurate …”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous needle placement and preoperative radiography may also represent a simple alternative to intraoperative fluoroscopy. Palpation or ultrasonography can also be used for site localization, with the latter being more accurate …”
Section: Discussionmentioning
confidence: 99%
“…These transducers emit ultrasound waves and receive the echoed signal that reflects off any structures it encounters ( 7 , 8 ). Studies have shown that diagnostic ultrasound yields more consistent and accurate diagnoses compared to traditional palpation methods, with a 10-fold increase in accuracy when using ultrasound in some applications ( 9 , 10 ). This can largely be attributed to the visual capabilities of ultrasound, where stiffness signals are quantitatively processed and displayed to the practitioner, unlike with traditional palpation where the clinician can only rely on qualitative metrics like physical touch.…”
Section: Introductionmentioning
confidence: 99%